Privacy Norms and Preferences for Photos Posted Online - Hoyle, Roberto; Stark, Luke; Ismail, Qatrunnada; Crandall, David; Kapadia, Apu; Anthony, Denise (ACM Transactions on Computer-Human Interaction, 2020)
We are surrounded by digital images of personal lives posted online. Changes in information and communication technologies (ICTs) have enabled widespread sharing of personal photos, increasing access to aspects of private life previously less observable. Most studies of privacy online explore differences in individual privacy preferences. Here we examine privacy perceptions of online photos considering both social norms, collectively-shared expectations of privacy, and individual preferences. We conducted an online factorial vignette study on Amazon Mechanical Turk (n=279). Our findings show that people share common expectations about the privacy of online images, and these privacy norms are socially contingent and multi-dimensional. Use of digital technologies to share personal photos is influenced by social context as well as individual preferences, while such sharing can affect the social meaning of privacy.